Acesso à literatura técnico-científica por discentes cegos da Universidade Federal do Pará - PINHEIRO, Alexandre Lobo (Universidade Federal do Pará, 2019)
People who have visual disabilities find many barriers to access to information, such as the technical-scientific literature, widely used by university students, because the lack of accessible bibliographic material is still big. This research intends to analyze the problems around the access to bibliographic material by blind students of Federal University of Pará. The general objective is to investigate the processes that involve the technical-scientific literature access by blind students of Federal University of Pará. The specifics are: a) To promote a discussion about the mediation of information to people with disabilities as a field of study in information science; b) To discuss about legal aspects and actions related to access to information for people with disabilities; c) To identify barriers and strategies for access to the technical-scientific literature of the blind students of Federal University of Pará; d) To analyze the processes that involve the mediation of the information for the technical-scientific literature access by blind students of Federal University of Pará. This is an exploratory study in which a case study will be carried out with theoretical contributions of the bibliographical survey and field research with data collection instruments through documents and interviews that can support the study. The interviews were taken to the blind Federal University of Pará students and the librarians who work in the Braille Space of the Central Library at UFPA. Based on the collected data, categories of analysis were established based on the declarations issued by the social subjects involved in comparison with the literature of the area of Information Science and those related to people with disabilities. The results show that in the process that involves access to the technical-scientific literature by blind UFPA students there are barriers in the scope of the student-teacher relationship and others related to the availability of bibliographical material in an accessible format. These barriers have negative consequences on the performance of these students in the development of their academic activities, as in the concept of the disciplines. It is concluded that overcoming these barriers depends on efforts already underway and more investments in factors with the potential to eliminate or overcome them as human resources, technology and interinstitutional partnerships.